2015
DOI: 10.1097/md.0000000000001306
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Expression of Cancer Stem Cell Markers and Poor Differentiation of Hepatocellular Carcinoma

Abstract: The role of cancer stem cell (CSC) markers in differentiation of hepatocellular carcinoma (HCC) remains uncertain. We conducted a meta-analysis to first investigate the association between expression of CSC markers (CD133, CD90, CD44, and EpCAM) and poor differentiation of HCC, and second, to determine if these CSC markers can be classified as biomarkers for patient classification and HCC differentiated therapy.The relevant literature was searched using PubMed, EMBASE, Elsevier, and Chinese Biological Medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Liu et al [29] indicated that CD90 might be more sensitive in predicting poor differentiation in HCC. Cheng et al [30] found that CD90 probably regulated the invasion and migration of liver cancer.…”
Section: Markers On the Cell Surface Or Membranous Proteinsmentioning
confidence: 99%
“…Liu et al [29] indicated that CD90 might be more sensitive in predicting poor differentiation in HCC. Cheng et al [30] found that CD90 probably regulated the invasion and migration of liver cancer.…”
Section: Markers On the Cell Surface Or Membranous Proteinsmentioning
confidence: 99%
“…[42] According to previous studies, CSCs were proven to exist in many solid tumors including glioma, melanoma, colon cancer, and hepatocellular carcinoma. [43,44] According to our knowledge, CSCs of gastric cancer were first isolated and identified in 2009 through the cell surface marker CD44. [45] Other cell surface markers of CSCs such as CD133, aldehyde dehydrogenase, CD24, and Sox2 (Sex determining Region Y-like high mobility group box-2) also have been used as diagnostic marker molecules on CSCs of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…14,19 Liu's group reported that CD90 has a specificity of 91.9% for HCC and a sensitivity of 48.22% for predicting poor differentiation. 62 In addition, TLR4-positive CSCs were found to be significantly greater in HCC tissues with microvascular invasion and strongly associated with both early recurrence and poor patient survival. 51 Thus, high expression of these markers is significantly associated with poor response to treatment and reduced survival, and measuring and/or monitoring liver CSCs in liver lesions or the peripheral circulation may be an effective tool for surveilling growth, metastasis and relapse of HCC.…”
Section: Function Of Liver Cscs For Diagnosis and Treatment Of Hccmentioning
confidence: 99%